DESAIN PENGISIAN TANGKI PENYIMPANAN AIR OTOMATIS MENGGUNAKAN SOLENOID VALVE BERBASIS ARDUINO DAN SENSOR AIR - maranti; Deosa Putra Caniago (LPPM-ITEBA, 2023)
The distribution of waterwhichis limited to certain hours, repairs andmaintenanceof water distribution pipescan causethe flowof water flowing fromthe company managing the water to housing to be disrupted, this results in disruption of activities that require clean water. The design of filling an automatic water storage drum using an Arduino microcontroller, a water sensor, a solenoid valve, and an LCD is expected to help in the design of automatic water drumfilling andcan help in storingwaterautomatically. In the designof anautomatic drum water storage device that has been made obtained the results of the success of the tool is 92%. With a success value of 92% it is expected that the design of this tool can help overcome the problem of the availability of clean water.